VIRAL MARKETING SUCCESS SECRETS: OPTIMISING SOCIAL MEDIA - Silvia Ekasari; Johni Eka Putra; Iwan Kusnadi (CV. Adiba Aisha Amira, 2024)
In today's increasingly competitive digital era, viral marketing through social media has become a key strategy for brands to increase their visibility and engagement. This research uses the literature study method. The results show that the success of viral marketing depends on several key factors: content creativity, a deep understanding of the target audience, good timing, and the ability to utilise the unique features of each social media platform. Major challenges include managing potential crises, maintaining brand consistency, and converting virality into measurable business results. As such, viral marketing through social media offers great potential for brands to achieve exponential growth in awareness and engagement. However, success depends on careful planning, precise execution, and the ability to adapt quickly to the platform's dynamics and ever-changing consumer behaviour. This research provides valuable insights for marketing practitioners and brand managers in designing and executing effective viral marketing strategies in today's digital age.